Singapore : Staff Report for 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
Outlook and risks. As Singapore prepares to celebrate its 50th anniversary in August, its economy continues to perform well. Despite the slow pace of the global recovery and a gradual decline in domestic credit growth and housing prices, projected economic growth of about 2.9 percent in 2015 is consistent with full employment and price stability. Growth is projected to slow down in the medium term, consistent with reduced reliance on foreign workers and rapid population aging. The authorities' new growth model takes into account Singapore's physical resource limits and aims to boost labor and land productivity. Risks to the baseline are tilted to the downside: Singapore's highly open economy is exposed to external shocks, most notably slower global growth and the side effects from volatility in global financial markets. Domestic vulnerabilities, including elevated private indebtedness, can amplify the impact of external shocks. Policies. In January, in response to a decline in expected inflation and a more uncertain outlook for growth, the Monetary Authority of Singapore (MAS) reduced the pace of appreciation of the nominal effective exchange rate (NEER) band. The more benign near?to medium-term inflation outlook warrants the relative easing of monetary policy. The monetary policy framework is robust and flexible but rising domestic leverage and heightened global interest rate and exchange rate volatility warrant heightened vigilance in assessing the balance of forces between the various channels of monetary policy. Singapore continues to maintain high regulatory and supervisory standards. Recent macroprudential measures have contributed to smoothing the cycle for credit and house prices. The budget's focus on boosting productivity, equality of opportunity, and inclusiveness is laudable, while the fiscal impulse is opportune given cyclical conditions. Restructuring and population aging. Building on Singapore's success and faced with high income inequality and the physical limits of a city state, the authorities have re-engineered the country's growth model to boost productivity while reducing reliance on foreign workers. The restructuring entails lower steady state growth and a shift in the functional distribution of income toward labor. Incentives provided for firms to increase productivity-enhancing investments and for Singaporeans to upgrade their skills should help ensure a successful transition. But slower potential growth and a lower share of profits in income could affect those investments, and gains in productivity could be realized only slowly. Flexibility in the application of foreign worker policies and continued review of incentives are warranted. The authorities are recalibrating fiscal policies with associated inter?and intra- generational impacts in order to proactively deal with Singapore's rapid population aging, enhance inclusiveness and reduce inequality, while remaining true to the principles of individual responsibility and sound public finances.